Embolizations of the hepatic tumors - two-year single center experience - Janczak, Dariusz; Zielińska, Dorota; Pawełczyk, Jerzy; Dorobisz, Tadeusz; Garcarek, Jerzy; Patrzałek, Dariusz; Chabowski, Mariusz (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Transcatheter arterial chemoembolization (TACE) and portal vein embolizations (PVE) are established methods of treatment of patients with hepatic tumors. The aim of the study was to present our experience in the treatment of liver tumors with embolization as a preliminary treatment for surgery or a part of palliative treatment. Methods. The analysis included 29 patients who had undergone 34 embolizations. Results. TACE was performed in 26 cases with hemangiomas in the unfavorable location, or mass effect and inoperable malignant tumors both primary and metastatic. PVE was performed in 8 cases with primary liver tumors and colon liver metastases.All included patients presented inoperable hepatic tumors. TACE was carried out in the patients with hepatocellular carcinoma (n = 1), cholangiocarcinoma (n = 1), metastatic tumor (n = 8), and hemangioma (n = 16), while PVE in the patients with cholangiocarcinoma (n = 2), metastatic tumor (n = 5) and neuroendocrine tumor (n = 1). The embolization was followed by surgery in the 5 PVE patients and 6 TACE patients. The postembolization syndrome was observed in 7 subjects. Death due to cancer progression occurred in the 4 PVE patients and 7 TACE patients. One patient died during TACE due to hemorrhagic shock. Conclusions. Right PVE and selective TACE are efficient for preliminary preparation of patients with healthy hepatic parenchyma for major liver resections, but the patients with liver cirrhosis require careful assessment. In the patients with hemangioma, embolization allows to avoid surgical treatment by reducing the lesion mass, or the extent of hepatic resection. The preliminary results of arterial embolizations with bleomycin, leading to tumor reduction in cases of giant liver hemangiomas are promising.